Lesson planning and teacher professional competence: mediation and moderation mechanisms in an integrative framework - Jurus Setiawan; Sutrisni Andayani; Sujino Sujino (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study aims to identify the mediation and moderation mechanisms that explain the relationship between lesson planning and teacher professional competence at the primary and secondary education levels, and to develop an integrative conceptual framework that addresses theoretical fragmentation in the literature. This Systematic Literature Review (SLR) follows the PRISMA 2020 protocol. A manual search was conducted using documented Boolean strings across the Scopus, ERIC, and Sinta databases, covering publications from 2016 to 2026. Inclusion criteria were established using the PEO (Population, Exposure, Outcome) framework. Study quality was assessed using the JBI Critical Appraisal Checklist. Inter-rater reliability was calculated using Cohen's kappa (κ = 0.87 for selection; κ = 0.89 for coding). Of 1,247 initially identified articles, 42 met the inclusion criteria and were analyzed using thematic analysis with deductive-inductive coding procedures. Synthesis of 42 studies revealed three primary mediation mechanisms: (1) deliberate reflection bridging planning practice with competence development; (2) integration of technological-pedagogical-content knowledge (TPACK) occurring during the planning process; and (3) enhanced self-efficacy through successful planning experiences. Three moderator categories were identified: internal factors (prior knowledge, experience, epistemic beliefs), external factors (collaborative supervision, professional development, communities of practice), and contextual factors (digital era, curriculum policy, resources). The proposed integrative framework positions lesson planning as a mediating process between teacher dispositions and professional competence, with contextual factors serving as moderators. The relationship between lesson planning and teacher professional competence is reciprocal and mediated by mechanisms of reflection, knowledge integration, and self-efficacy. However, causal claims within this framework remain largely theoretical propositions requiring empirical validation through longitudinal and experimental studies.